Administrators' Application of Physical Resources Management Strategies for Secondary Schools' Effectiveness in Anambra State - ONUH, UCHENNA REBECCA; EZIUZO, GLORIA OLACHUKWU; EKWEOGU, LOVELINE BENATAOKWU (International Journal of Educational Management, 2021)
The poor and devastating state of physical resources in secondary schools in Anambra State which seem to hinder teachers' proficiency and students' learning has warranted the present study. Given the importance of physical resources for schools effectiveness, this study however examined administrators' application of physical resources management strategies for secondary schools effectiveness in Anambra State. Four research questions guided the study. Adescriptive survey research design was employed in the study. Population of the study constituted 259 principals from the 259 public secondary schools located within 6 education zones in Anambra State. Sample size of the study comprised 130 principals from 130 public secondary schools, selected out of the entire principals' population at 10% (percent) using stratified random sampling technique. A 24-item questionnaire titled “Administrators' Application of Physical Resources Management Strategies for Secondary Schools Effectiveness Questionnaire (AAPRMSSSEQ)” developed by the researchers served as instrument for data collection. The research instrument was validated by three experts and reliability of the instrument established through a pilot-test. Data collated were analyzed using mean scores and standard deviation. Findings of the study revealed that the secondary school administrators' did not effectively apply the various physical resources management strategies that is; the routine, emergency, preventive and corrective management strategies. Among the recommendations proffered from the findings of the study are that the Anambra State Government and Post Primary Schools Service Commission (PPSSC) should encourage administrators application of physical resources management strategies for secondary schools effectiveness in Anambra State through adequate funding, supervision and retraining programmes.